A Storm Drifting by? Defamation Law and Sport in Australia and New Zealand - Davies, Chris (Victoria University of Wellington Law Review, 2009)
The law of defamation provides protection to people's reputations. An examination of the sports-related defamation cases in Australia and New Zealand indicates that such claims have been based on written comments, spoken words and also visual images. These cases can be internal comments made by those involved in a sport, as illustrated by the recent comments made by the coach of the Melbourne Storm, Craig Bellamy. However, as the recently decided case of Coates v Harbour Radio Pty Ltd indicates, most of the cases have involved comments made by people in the media rather than within the sport. An examination of defamation and sport, therefore, requires an examination of the sometimes delicate balance between the media's desire to report and comment on controversial sporting matters, and the desire of those involved in sport wishing to protect their reputations.